A Noncoding Regulatory RNAs Network Driven by Circ‐CDYL Acts Specifically in the Early Stages Hepatocellular Carcinoma. Issue 1 (11th August 2019) - Wei, Yanping; Chen, Xin; Liang, Chi; Ling, Yan; Yang, Xinwei; Ye, Xiaofei; Zhang, Hailing; Yang, Pinghua; Cui, Xiuliang; Ren, Yibing; Xin, Xianglei; Li, Hengyu; et al.
Abstract : Hepatocellular carcinoma (HCC) is one of the fastest‐rising causes of cancer‐related death worldwide, but its deficiency of specific biomarkers and therapeutic targets in the early stages lead to severe inadequacy in the early diagnosis and treatment of HCC. Covalently closed circular RNA (circRNA), which was once considered an aberrant splicing by‐product, is now drawing new interest in cancer research because of its remarkable functionality. Beneath the surface of the dominant functional proteins events, a hidden circRNA‐centric noncoding regulatory RNAs network active in the very early stage of HCC is here revealed by a genome‐wide analysis of mRNA, circRNA, and microRNA (miRNA) expression profiles. Circ‐CDYL (chromodomain Y like) is specifically up‐regulated in the early stages of HCC and therefore contributes to the properties of epithelial cell adhesion molecule (EPCAM)‐positive liver tumor‐initiating cells. Circ‐CDYL interacts with mRNAs encoding hepatoma‐derived growth factor (HDGF) and hypoxia‐inducible factor asparagine hydroxylase (HIF1AN) by acting as the sponge of miR‐892a and miR‐328‐3p, respectively. Subsequently, activation of the phosphoinositide 3‐kinase (PI3K)‐AKT serine/threonine kinase‐mechanistic target of rapamycin kinase complex 1/β‐catenin and NOTCH2 pathways, which promote the expression of the effect proteins, baculoviral IAP repeat containing 5 (BIRC5 or SURVIVIN) and MYC proto‐oncogene, is influenced by circ‐CDYL. A treatment incorporating circ‐CDYL interference and traditional enzyme inhibitors targeting PI3K and HIF1AN demonstrated highly effective inhibition of stem‐like characteristics and tumor growth in HCC. Finally, we demonstrated that circ‐CDYL expression or which combined with HDGF and HIF1AN are both independent markers for discrimination of early stages of HCC with the odds ratios of 1.09 (95% confidence interval [CI], 1.02‐1.17) and 124.58 (95% CI, 13.26‐1170.56), respectively. Conclusion: These findings uncover a circRNA‐centric noncoding regulatory RNAs network in the early stages of HCC and thus provide a possibility for surveillance and early treatment of HCC.